A monthly regression correction model for the Hargreaves–Samani method in Mainland China. (7th April 2020) - Xia, Xingsheng; Zhu, Xiufang; Pan, Yaozhong; Zhang, Jinshui
Abstract: Reference crop evapotranspiration (ET0 ) is an important parameter for irrigation engineering. It can be calculated using the Penman–Monteith method (PM), which results in ET0‐PM . This study uses ET0‐PM to determine the availability of a monthly linear regression correction model for the Hargreaves–Samani method (HG). The data were obtained from 647 meteorological stations in mainland China, which are contained within the data set of monthly values of climate data from Chinese surface stations. For most stations, the correlation coefficient of ET0‐PM and ET0‐HG (determined by the HG method) ranges from 0.5 to 1.0. This provides the necessary conditions for the monthly linear regression correction of ET0‐HG . The mean relative change of the mean absolute error before and after the ET0‐HG correction for each year indicates that the scheme adopted in this study yields improved correction results during autumn, winter and spring in mainland China and poor results during summer. However, the monthly regression correction model for the HG is only available for part of the stations in each season. This study supplements a case for the larger‐scale ET0‐HG monthly regression correction. This can be a reference for the further refinement of the ET0‐HG spatio‐temporal correction © 2020 John Wiley & Sons, Ltd. Résumé: L'évapotranspiration des cultures de référence (ET0 ) est un paramètre important pour l'ingénierie de l'irrigation. ET0 peut être calculé à l'aide de la méthode Penman–Monteith (PM), qui donne ET0‐PM . Cette étude utilise ET0‐PM pour déterminer la disponibilité d'un modèle de correction de régression linéaire mensuel pour la méthode Hargreaves–Samani (HG). Les données ont été obtenues de 647 stations météorologiques en Chine continentale, qui sont contenues dans l'ensemble de données des valeurs mensuelles des données climatiques des stations de surface chinoises. Pour la plupart des stations, le coefficient de corrélation ET0‐PM et ET0‐HG (déterminé par la méthode HG) varie de 0.5 à 1.0. Cela fournit les conditions nécessaires pour la correction de régression linéaire mensuelle de ET0‐HG . La variation relative moyenne de l'erreur absolue moyenne avant et après la correction ET0‐HG pour chaque année indique que le schéma adopté dans cette étude donne de meilleurs résultats de correction en automne, en hiver et au printemps en Chine continentale et de mauvais résultats en été. Cependant, le modèle de correction de régression mensuelle pour le HG n'est disponible que pour une partie des stations à chaque saison. Cette étude complète un cas pour la correction de régression mensuelle à plus grande échelle de ET0‐HG . Cela peut être une référence pour le perfectionnement de la correction spatio‐temporelle ET0‐HG . © 2020 John Wiley & Sons, Ltd.